Concealment of identity by adopting transgender attire - Kumar, Gautam; Kumar, Vivek; Prasad, Rajib; Kumar Deb , Prabir (Journal of Indian Academy of Forensic Medicine, 2019)
Identification is the individuality of a person and knowing the gender forms an important parameter for it. The practice of transvestism  makes concealment of identity very easy. In an interesting Case report form North Bengal Medical College & Hospital, three  transgenders were arrested by GRPfor carrying illegal arms and ammunition. They were taken to North Bengal Medical College &  Hospital for medical examination where we found all of them concealed their gender by adopting female attire. After general physical  examination, radiological examination and karyotyping from buccal mucosa, it was concluded that all the three persons were  genetically as well as phenotypically male.
Keywords: Concealment of identity; Transgender; Transvestism; Y' Chromosome; Testicular Volume